Performance of semi skilled workers in electric and electronic industry within Iskandar Malaysia: a comparison between local and Indonesian / Mohd Zaki Sadik (Faculty of Business and Management, 2008)
The objective of this study is to examine the relationship between Motivation, Ability and Working Environment towards the performance of semi skills workers in Electric and Electronics manufacturing industry, to compare the job performance between Indonesian and local workers and to compare three factors of job performance between Indonesian and local workers. In order to achieve the objectives, the researcher has distributed 50 questionnaires to each Indonesian and locals. Next, the researcher used Cross-Tabulation analysis to examine the relationship between independent variables and dependent variable. As for comparing level of job performance and three factors of job performance, the researcher used Paired Sample Statistical analysis. The result indicates that there is a significant relationship between motivation, ability and working environment with job performance. This result is supported by Bruche H.Clark,Andrew V. Abela and Tim Ambler (2005) for motivation and ability and Solveig Osborg Ose (2004) for working environment. While, the result on comparing Job Performance between Indonesian and local workers indicates that Indonesian workers perform better in their jobs. It is the same as Job Performance factor where Indonesian workers are more motivated and have more ability compare to local workers. Meanwhile for adaptability with Working Environment, local workers are adapting better compared to Indonesian workers.